Solve for m m/-3=-5-18

Math
m-3=-5-18
Multiply both sides of the equation by -3.
-3⋅m-3=-3⋅(-5-18)
Simplify both sides of the equation.
Tap for more steps…
Simplify -3⋅m-3.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Factor 3 out of -3.
3(-1)⋅m-3=-3⋅(-5-18)
Factor 3 out of -3.
3⋅-1⋅m3⋅-1=-3⋅(-5-18)
Cancel the common factor.
3⋅-1⋅m3⋅-1=-3⋅(-5-18)
Rewrite the expression.
-1⋅m-1=-3⋅(-5-18)
-1⋅m-1=-3⋅(-5-18)
Simplify the expression.
Tap for more steps…
Move the negative one from the denominator of m-1.
-1⋅(-1⋅m)=-3⋅(-5-18)
Rewrite -1⋅m as -m.
-1⋅(-m)=-3⋅(-5-18)
-1⋅(-m)=-3⋅(-5-18)
Multiply -1(-m).
Tap for more steps…
Multiply -1 by -1.
1m=-3⋅(-5-18)
Multiply m by 1.
m=-3⋅(-5-18)
m=-3⋅(-5-18)
m=-3⋅(-5-18)
Simplify -3⋅(-5-18).
Tap for more steps…
Subtract 18 from -5.
m=-3⋅-23
Multiply -3 by -23.
m=69
m=69
m=69
Solve for m m/-3=-5-18

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top